Novel sulfonated hydrophilic indium(III) and gallium(III) phthalocyanine photosensitizers: preparation and investigation of photophysicochemical properties - Guzel, Emre; Atmaca, Goknur Yasa; Erdogmus, Ali; Kocak, Makbule Burkut (TAYLOR & FRANCIS LTD, 2017)
The new tetra-non-peripherally benzenesulfonic acid-substituted hydrophilic gallium chloride and indium chloride phthalocyanine complexes have been synthesized by cyclotetramerization of 4-(2,3-dicyanophenyl)benzenesulfonic acid (1). The newly synthesized phthalocyanines have been characterized by Fourier transform infrared spectroscopy, proton nuclear magnetic resonance, mass and UV-vis spectroscopy techniques. The water-soluble gallium(III) phthalocyanine derivative (2) was aggregated in aqueous media but was fully disaggregated in the presence of a surfactant Triton X-100. The incorporation of sulfonate moieties of the phthalocyanine macrocycle provides hydrophilic character to the new compounds, which is useful for drug administration and serves as crucial in PDT application. So, the photochemical properties (singlet oxygen quantum yields and photodegradation quantum yields) and photophysical properties (fluorescence behavior) of the complexes were reported in different solutions (DMSO and water). The results of spectral measurements showed that both np-GaPc (2) and np-InPc (3) can be used as sensitizers in PDT because of their singlet oxygen efficiencies. [GRAPHICS] .
Keywords: Sulfonated anionic phthalocyanines; hydrophilic; water-soluble; flourescence; photochemistry; WATER-SOLUBLE PHTHALOCYANINES; MICROWAVE-ASSISTED SYNTHESIS; SUBSTITUTED PHTHALOCYANINES; ALUMINUM PHTHALOCYANINES; PHOTODYNAMIC ACTIVITY; AMPHIPHILIC PHTHALOCYANINES; ZINC PHTHALOCYANINES; AQUEOUS-SOLUTIONS; AGGREGATION; THERAPY; Chemistry